In Reviews We Trust: But Should We? Experiences with Physician Review Websites - Kersting, Joschka; Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 4th International Conference on Internet of Things, Big Data and Security)
The ability to openly evaluate products, locations and services is an achievement of the Web 2.0. It has never been easier to inform oneself about the quality of products or services and possible alternatives. Forming one’s own opinion based on the impressions of other people can lead to better experiences. However, this presupposes trust in one’s fellows as well as in the quality of the review platforms. In previous work on physician reviews and the corresponding websites, it was observed that there occurs faulty behavior by some reviewers and there were noteworthy differences in the technical implementation of the portals and in the efforts of site operators to maintain high quality reviews. These experiences raise new questions regarding what trust means on review platforms, how trust arises and how easily it can be destroyed.
Keywords: Trust; Physician Reviews; Network Analysis

Quantifying the Impact of Geospatial Recommendations: A Field Experiment in High Street Retail - Betzing, Jan H.; Bartelheimer, Christian; Niemann, Marco; Berendes, Carsten Ingo; Beverungen, Daniel (Proceedings of the 27th European Conference on Information Systems (ECIS))

Context- and Data-driven Satisfaction Analysis of User Interface Adaptations Based on Instant User Feedback - Yigitbas, Enes; Hottung, André; Mansfield Rojas, Sebastian; Anjorin, Anthony; Sauer, Stefan; Engels, Gregor (Proceedings of the ACM on Human-Computer Interaction)

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Conceptualizing the Impact of Workarounds – An Organizational Routines’ Perspective - Wolf, Verena; Beverungen, Daniel (Proceedings of the 27th European Conference on Information Systems (ECIS))
Employees’ acceptance and resistance of new technology and social structure are frequently examined in Information Systems research. Resistance is expressed in various forms, including a lack of cooperation, workarounds, and physical sabotage. Workarounds, in particular, have a dual nature and can refer to both, undesirable behavior that contradicts organizational struc-ture and to desired organizational innovation. While antecedents and different forms of worka-rounds have been explored, literature has remained silent on how and why workarounds of an individual employee can affect activities performed by other employees and thereby, change work routines on an organizational level. Since employees’ day-to-day performances constitute the ostensive patterns of a routine, we argue that workarounds will not only impact performanc-es of adjacent routines, but also transform the organization as a social structure. With a prelim-inary set of qualitative data from 24 interviews, we used a multiple case study design to concep-tualize six patterns that illustrate how and why workarounds can spread through an organiza-tion. The patterns are systematized by a framework that considers three types of collaboration and two types of handoffs across routines. This first evidence points at the nature of complex desired and undesired consequences that can emerge through workarounds performed in an organization.
Keywords: Resistance; Workaround; Organizational Routines; Structuration Theory

Zinc oxide based dielectric nanoantennas for efficient nonlinear frequency conversion - Golla, C.; Weber, N.; Meier, Cedrik (Journal of Applied Physics)

Ambidexterity in Service Innovation Research: A Systematic Literature Review - Wolf, Verena (Proceedings of the 14th International Conference on Wirtschaftsinformatik)
Increased interconnectedness of multiple actors and digital resources in service eco-systems offer new opportunities for service innovation. In digitally transforming eco-systems, organizations need to explore and exploit innovation simultaneously, which is defined as ambidexterity. However, research on ambidextrous service innovation is scarce. We provide a systematic literature review based on the concepts of ambidexterity, offering two contributions. First, research strands are disconnected, emphasizing either exploration or exploitation of service innovation, despite an organizations’ need to accelerate innovation cycles of exploring and exploiting services. Second, a new framework for ambidextrous service innovation is provided, inspired by the dynamism and generative mechanisms of the ontologically related concept of organizational routines. The framework adopts the perspective of a mutually constitutive relationship between exploring new and exploiting current resources, activities, and knowledge. The findings remedy the scattered literature through a coherent perspective on service innovation that responds to organizations’ needs and guides future research.
Keywords: Exploration; Exploitation; Service Innovation; Organizational Routines; Ambidexterity

Characterization of the linear-acoustic material behavior of fiber-reinforced composites using lamb waves - Johannesmann, Sarah; Webersen, Manuel; Düchting, Julia; Claes, Leander; Henning, Bernd (45th Annual Review of Progress in Quantitative Nondestructive Evaluation)

Victorian Ideologies in Contemporary British Cultures

(New?) Masculinities in Nineteenth-Century Sensation Fiction and Contemporary Black British Fiction - Flotmann-Scholz, Christina; Lienen, Anna (Victorian Ideologies in Contemporary British Cultures)

Introduction - Flotmann-Scholz, Christina; Lienen, Anna (Victorian Ideologies in Contemporary British Cultures)

Money Makes the Reviewer Go Round – Ambivalent Effects of Online Review Elicitation in B2B Markets - Neumann, Jürgen; Gutt, Dominik (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

When does Local Status Matter? – The Relationship between Reviewer Location and Perceived Usefulness of Online Reviews - Neumann, Jürgen; Gutt, Dominik; Görzen, Thomas; Kundisch, Dennis (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

Reviewing the Vendor or the Product – Analyzing Vendor versus Product Representation in B2B Review Systems - Poniatowski, Martin; Neumann, Jürgen; Kundisch, Dennis (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

Organizing Their Thoughts – How Online Review Templates Affect the Review Text - Poniatowski, Martin; Neumann, Jürgen; Görzen, Thomas; Kundisch, Dennis (Proceedings of the 27th European Conference on Information Systems (ECIS))

The Virtues of Anonymity - An Empirical Investigation of the Relationship between B2B Online Ratings and Reviewer Self-Disclosure - Gutt, Dominik; Neumann, Jürgen (Proceedings of the 27th European Conference on Information Systems (ECIS))

He Who Pays the Piper Calls the Tune: Online Review Elicitation by Sellers and Third-Party Platforms in B2B Markets - Neumann, Jürgen; Gutt, Dominik (Proceedings of the 27th European Conference on Information Systems (ECIS))

Do Digital Startups Prepare for Technology Pivots? - An Initial Analysis of Job Adverts - Bohn, Nicolai (Proceedings of the 25th Americas Conference on Information Systems (AMCIS))

Digitale Modellierungen sozialer Räume - Herzig, Bardo; Klar, Tilman-Mathies (Digitale Transformation in der Bildungslandschaft- den analogen Stecker ziehen?)

Service Function Chaining Across OpenStack and Kubernetes Domains - Razzaghi Kouchaksaraei, Hadi; Karl, Holger (13th ACM International Conference on Distributed and Event-based Systems)
Remarkable advantages of Containers (CNs) over Virtual Machines (VMs) such as lower overhead and faster startup has gained the attention of Communication Service Providers (CSPs) as using CNs for providing Virtual Network Functions (VNFs) can save costs while increasing the service agility. However, as it is not feasible to realise all types of VNFs in CNs, the coexistence of VMs and CNs is proposed. To put VMs and CNs together, an orchestration framework that can chain services across distributed and heterogeneous domains is required. To this end, we implemented a framework by extending and consolidating state-of-the-art tools and technologies originated from Network Function Virtualization (NFV), Software-defined Networking (SDN) and cloud computing environments. This framework chains services provisioned across Kubernetes and OpenStack domains. During the demo, we deploy a service consist of CN- and VM-based VNFs to demonstrate different features provided by our framework.
Keywords: Network Function Virtualization; Software-defined Networking; Cloud Computing; service orchestration; OpenStack; Kubernetes

Victorian Ideologies in Contemporary British Cultures

Privacy-friendly User Location Tracking with Smart Devices: The BeaT Prototype - Betzing, Jan H; Niemann, Marco; Berendes, Carsten Ingo (Human Practice. Digital Ecologies. Our Future. - Tagungsband der 14. Internationalen Tagung Wirtschaftsinformatik (WI 2019))

Empowering Network Service Developers: Enhanced NFV DevOps and Programmable MANO - Soenen, Thomas; Tavernier, Wouter; Peuster, Manuel; Vicens, Felipe; Xilouris, George; Kolometsos, Stavros; Kourtis, Michail-Alexandros; Colle, Didier (IEEE Communications Magazine)

Introducing Automated Verification and Validation for Virtualized Network Functions and Services - Peuster, Manuel; Schneider, Stefan Balthasar; Zhao, Mengxuan; Xilouris, George; Trakadas, Panagiotis; Vicens, Felipe; Tavernier, Wouter; Soenen, Thomas; Vilalta, Ricard; Andreou, George; Kyriazis, Dimosthenis; Karl, Holger (IEEE Communications Magazine)

A high dynamic range optical detector for measuring single photons and bright light - Tiedau, Johannes; Meyer-Scott, Evan; Nitsche, Thomas; Barkhofen, Sonja; Bartley, Tim; Silberhorn, Christine (Optics Express)

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Secular stagnation? Is there statistical evidence of an unprecedented, systematic decline in growth? - Fritz, Marlon; Gries, Thomas; Feng, Yuanhua (Economics Letters)

On-the-fly Usability Evaluation of Mobile Adaptive UIs through Instant User Feedback - Yigitbas, Enes; Jovanovikj, Ivan; Josifovska, Klementina; Sauer, Stefan; Engels, Gregor (Proceedings of the 17th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT 2019))

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Competition and Online Rating Distributions - Gutt, Dominik; Herrmann, Philipp; Rahman, Mohammad (Information Systems Research)

Can Experience be Trusted? Investigating the Effect of Experience on Decision Biases in Crowdworking Platforms - Görzen, Thomas (Proceedings of the 52nd Hawaii International Conference on System Sciences (HICSS))

Wertgenerierung bei M&A Transaktionen durch Bekanntgabe von Synergien? - Mehring, Oliver; Sievers, Sönke; Keienburg, Georg; Kengelbach, Jens
Öffentlich gelistete Firmen, die die Mehrheit an anderen börsennotierten Unternehmen er-werben und den Kapitalmarkt an den Synergieerwartungen teilhaben lassen, werden mit höheren kumulativen abnormalen Renditen im Ankündigungszeitpunkt belohnt verglichen mit solchen Unternehmen, die diese geheim halten. Des Weiteren ist die empirische Evi-denz konsistent mit der Idee, dass diese Käuferunternehmen ihre Transaktionen besser in-tegrieren, weil auch die industrieadjustierten Ein- und Zweijahresrenditen der ankündigen-den Unternehmen ökonomisch und statistisch signifikant höher sind als die der zurückhal-tenden Käuferfirmen.

Multi-unit Bilateral Trade - Lazos, Philip; Goldberg, Paul; Skopalik, Alexander; Gerstgrasser, Matthias; de Keijzer, Bart (Proceedings of the Thirty-Third AAAI Conference on Artificial Intelligence (AAAI))
We characterise the set of dominant strategy incentive compatible (DSIC), strongly budget balanced (SBB), and ex-post individually rational (IR) mechanisms for the multi-unit bilateral trade setting. In such a setting there is a single buyer and a single seller who holds a finite number k of identical items. The mechanism has to decide how many units of the item are transferred from the seller to the buyer and how much money is transferred from the buyer to the seller. We consider two classes of valuation functions for the buyer and seller: Valuations that are increasing in the number of units in possession, and the more specific class of valuations that are increasing and submodular. Furthermore, we present some approximation results about the performance of certain such mechanisms, in terms of social welfare: For increasing submodular valuation functions, we show the existence of a deterministic 2-approximation mechanism and a randomised e/(1-e) approximation mechanism, matching the best known bounds for the single-item setting.

Using High Performance Computing for Unrelated Parallel Machine Scheduling with Sequence-Dependent Setup Times: Development and Computational Evaluation of a Parallel Branch-and-Price Algorithm - Rauchecker, Gerhard; Schryen, Guido (Computers & Operations Research)
Scheduling problems are essential for decision making in many academic disciplines, including operations management, computer science, and information systems. Since many scheduling problems are NP-hard in the strong sense, there is only limited research on exact algorithms and how their efficiency scales when implemented on parallel computing architectures. We address this gap by (1) adapting an exact branch-and-price algorithm to a parallel machine scheduling problem on unrelated machines with sequence- and machine-dependent setup times, (2) parallelizing the adapted algorithm by implementing a distributed-memory parallelization with a master/worker approach, and (3) conducting extensive computational experiments using up to 960 MPI processes on a modern high performance computing cluster. With our experiments, we show that the efficiency of our parallelization approach can lead to superlinear speedup but can vary substantially between instances. We further show that the wall time of serial execution can be substantially reduced through our parallelization, in some cases from 94 hours to less than six minutes when our algorithm is executed on 960 processes.
Keywords: parallel machine scheduling with setup times; parallel branch-and-price algorithm; high performance computing; master/worker parallelization

Walking the Middle Path: How Medium Trade-off Exposure Leads to Higher Consumer Satisfaction in Recommender Agents - Schuhbeck, Veronika; Siegfried, Nils; Dorner, Verena; Benlian, Alexander; Scholz, Michael; Schryen, Guido (Proceedings of the 14. Internationale Tagung Wirtschaftsinformatik)
Recommender Agents (RAs) facilitate consumers’ online purchase decisions for complex, multi-attribute products. As not all combinations of attribute levels can be obtained, users are forced into trade-offs. The exposure of trade-offs in a RA has been found to affect consumers’ perceptions. However, little is known about how different preference elicitation methods in RAs affect consumers by varying degrees of trade-off exposure. We propose a research model that investigates how different levels of trade-off exposure cognitively and affectively influence consumers’ satisfaction with RAs. We operationalize these levels in three different RA types and test our hypotheses in a laboratory experiment with 116 participants. Our results indicate that with increasing tradeoff exposure, perceived enjoyment and perceived control follow an inverted Ushaped relationship. Hence, RAs using preference elicitation methods with medium trade-off exposure yield highest consumer satisfaction. This contributes to the understanding of trade-offs in RAs and provides valuable implications to e-commerce practitioners.
Keywords: Recommender Agents; Preference Elicitation Method; Trade-off Exposure; Customer Satisfaction

Bewertung von Maschinen-generierten Geschäftsmodell-Ideen: Eine experimentelle Untersuchung - Seutter, Janina

Growth Trends and Systematic Patterns of Boom and Busts –Testing 200 Years of Business Cycle Dynamics - Gries, Thomas; Fritz, Marlon; Yuanhua, Feng (Oxford Bulletin of Economics and Statistics)

Heart over Heels? An Empirical Analysis of the Relationship between Emotions and Review Helpfulness for Experience and Credence Goods - Müller, Michelle; Gutt, Dominik (Wirtschaftsinformatik Proceedings 2019)

A Semi-Automated Approach for Generating Online Review Templates, - Poniatowski, Martin; Neumann, Jürgen; Görzen, Thomas; Kundisch, Dennis (Wirtschaftsinformatik Proceedings 2019)

Power Allocation with a Wireless Multi-cast Aware Routing for Virtual Network Embedding - Afifi, Haitham; Karl, Holger (2019 16th IEEE Annual Consumer Communications & Networking Conference (CCNC2019))

Always be Two Steps Ahead of Your Enemy - Maintaining a Routable Overlay under Massive Churn with an Almost Up-to-date Adversary - Götte, Thorsten; Vijayalakshmi, Vipin Ravindran; Scheideler, Christian (Proceedings of the 2019 IEEE 33rd International Parallel and Distributed Processing Symposium (IPDPS '19))
We investigate the maintenance of overlay networks under massive churn, i.e. nodes joining and leaving the network. We assume an adversary that may churn a constant fraction $α n$ of nodes over the course of $\mathcal{O}(\log n)$ rounds. In particular, the adversary has an almost up-to-date information of the network topology as it can observe an only slightly outdated topology that is at least $2$ rounds old. Other than that, we only have the provably minimal restriction that new nodes can only join the network via nodes that have taken part in the network for at least one round. Our contributions are as follows: First, we show that it is impossible to maintain a connected topology if adversary has up-to-date information about the nodes' connections. Further, we show that our restriction concerning the join is also necessary. As our main result present an algorithm that constructs a new overlay- completely independent of all previous overlays - every $2$ rounds. Furthermore, each node sends and receives only $\mathcal{O}(\log^3 n)$ messages each round. As part of our solution we propose the Linearized DeBruijn Swarm (LDS), a highly churn resistant overlay, which will be maintained by the algorithm. However, our approaches can be transferred to a variety of classical P2P Topologies where nodes are mapped into the $[0,1)$-interval.

Energy Efficient Parallel K-Means Clustering for an Intel® Hybrid Multi-Chip Package - Souza, Matheus A.; Maciel, Lucas A.; Penna, Pedro Henrique; Freitas, Henrique C. (2018 30th International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD))
FPGA devices have been proving to be good candidates to accelerate applications from different research topics. For instance, machine learning applications such as K-Means clustering usually relies on large amount of data to be processed, and, despite the performance offered by other architectures, FPGAs can offer better energy efficiency. With that in mind, Intel has launched a platform that integrates a multicore and an FPGA in the same package, enabling low latency and coherent fine-grained data offload. In this paper, we present a parallel implementation of the K-Means clustering algorithm, for this novel platform, using OpenCL language, and compared it against other platforms. We found that the CPU+FPGA platform was more energy efficient than the CPU-only approach from 70.71% to 85.92%, with Standard and Tiny input sizes respectively, and up to 68.21% of performance improvement was obtained with Tiny input size. Furthermore, it was up to 7.2×more energy efficient than an Intel® Xeon Phi ™, 21.5×than a cluster of Raspberry Pi boards, and 3.8×than the low-power MPPA-256 architecture, when the Standard input size was used.
Keywords: pc2-harp-ressources

Automatic Mapping of the Sum-Product Network Inference Problem to FPGA-Based Accelerators - Sommer, Lukas; Oppermann, Julian; Molina, Alejandro; Binnig, Carsten; Kersting, Kristian; Koch, Andreas (2018 IEEE 36th International Conference on Computer Design (ICCD))
In recent years, FPGAs have been successfully employed for the implementation of efficient, application-specific accelerators for a wide range of machine learning tasks. In this work, we consider probabilistic models, namely, (Mixed) Sum-Product Networks (SPN), a deep architecture that can provide tractable inference for multivariate distributions over mixed data-sources. We develop a fully pipelined FPGA accelerator architecture, including a pipelined interface to external memory, for the inference in (mixed) SPNs. To meet the precision constraints of SPNs, all computations are conducted using double-precision floating point arithmetic. Starting from an input description, the custom FPGA-accelerator is synthesized fully automatically by our tool flow. To the best of our knowledge, this work is the first approach to offload the SPN inference problem to FPGA-based accelerators. Our evaluation shows that the SPN inference problem benefits from offloading to our pipelined FPGA accelerator architecture.
Keywords: pc2-harp-ressources

Automated Feature Engineering on Time Series Data - Lienen, Julian

Constructing Concurrent Data Structures on FPGA with Channels - Yan, Hui; Li, Zhaoshi; Liu, Leibo; Yin, Shouyi; Wei, Shaojun (Proceedings of the 2019 ACM/SIGDA International Symposium on Field-Programmable Gate Arrays)
The performance of High-Level Synthesis (HLS) applications with irregular data structures is limited by its imperative programming paradigm like C/C++. In this paper, we show that constructing concurrent data structures with channels, a programming construct derived from CSP (communicating sequential processes) paradigm, is an effective approach to improve the performance of these applications. We evaluate concurrent data structure for FPGA by synthesizing a K-means clustering algorithm on the Intel HARP2 platform. A fully pipelined KMC processing element can be synthesized from OpenCL with the help of a SPSC (single-producer-single-consumer) queue and stack built from channels, achieving 15.2x speedup over a sequential baseline. The number of processing element can be scaled up by leveraging a MPMC (multiple-producer-multiple-consumer) stack with work distribution for dynamic load balance. Evaluation shows that an additional 3.5x speedup can be achieved when 4 processing element is instantiated. These results show that the concurrent data structure built with channels has great potential for improving the parallelism of HLS applications. We hope that our study will stimulate further research into the potential of channel-based HLS.
Keywords: pc2-harp-ressources

Combining Multiple Optimized FPGA-based Pulsar Search Modules Using OpenCL - Wang, Haomiao; Thiagaraj, Prabu; Sinnen, Oliver (Journal of Astronomical Instrumentation)
Field-Programmable Gate Arrays (FPGAs) are widely used in the central signal processing design of the Square Kilometer Array (SKA) as hardware accelerators. The frequency domain acceleration search (FDAS) module is an important part of the SKA1-MID pulsar search engine. To develop for a yet to be finalized hardware, for cross-discipline interoperability and to achieve fast prototyping, OpenCL as a high-level FPGA synthesis approaches employed to create the sub-modules of FDAS. The FT convolution and the harmonic-summing plus some other minor sub-modules are elements in the FDAS module that have been well-optimized separately before. In this paper, we explore the design space of combining well-optimized designs, dealing with the ensuing need to trade-off and compromise. Pipeline computing is employed to handle multiple input arrays at high speed. The hardware target is to employ multiple high-end FPGAs to process the combined FDAS module. The results show interesting consequences, where the best individual solutions are not necessarily the best solutions for the speed of a pipeline where FPGA resources and memory bandwidth need to be shared. By proposing multiple buffering techniques to the pipeline, the combined FDAS module can achieve up to 2[Formula: see text] speedup over implementations without pipeline computing. We perform an extensive experimental evaluation on multiple high-end FPGA cards hosted in a workstation and compare to a technology comparable mid-range GPU.
Keywords: pc2-harp-ressources

Mapping a Guided Image Filter on the HARP Reconfigurable Architecture Using OpenCL - Faict, Thomas; D’Hollander, Erik H.; Goossens, Bart (Algorithms)
Intel recently introduced the Heterogeneous Architecture Research Platform, HARP. In this platform, the Central Processing Unit and a Field-Programmable Gate Array are connected through a high-bandwidth, low-latency interconnect and both share DRAM memory. For this platform, Open Computing Language (OpenCL), a High-Level Synthesis (HLS) language, is made available. By making use of HLS, a faster design cycle can be achieved compared to programming in a traditional hardware description language. This, however, comes at the cost of having less control over the hardware implementation. We will investigate how OpenCL can be applied to implement a real-time guided image filter on the HARP platform. In the first phase, the performance-critical parameters of the OpenCL programming model are defined using several specialized benchmarks. In a second phase, the guided image filter algorithm is implemented using the insights gained in the first phase. Both a floating-point and a fixed-point implementation were developed for this algorithm, based on a sliding window implementation. This resulted in a maximum floating-point performance of 135 GFLOPS, a maximum fixed-point performance of 430 GOPS and a throughput of HD color images at 74 frames per second.
Keywords: pc2-harp-ressources

Parallel multiprocessing and scheduling on the heterogeneous Xeon+FPGA platform - Rodríguez, Andrés; Navarro, Angeles; Asenjo, Rafael; Corbera, Francisco; Gran, Rubén; Suárez, Darío; Nunez-Yanez, Jose (The Journal of Supercomputing)
Heterogeneous computing that exploits simultaneous co-processing with different device types has been shown to be effective at both increasing performance and reducing energy consumption. In this paper, we extend a scheduling framework encapsulated in a high-level C++ template and previously developed for heterogeneous chips comprising CPU and GPU cores, to new high-performance platforms for the data center, which include a cache coherent FPGA fabric and many-core CPU resources. Our goal is to evaluate the suitability of our framework with these new FPGA-based platforms, identifying performance benefits and limitations.We target the state-of-the-art HARP processor that includes 14 high-end Xeon classes tightly coupled to a FPGA device located in the same package. We select eight benchmarks from the high-performance computing domain that have been ported and optimized for this heterogeneous platform. The results show that a dynamic and adaptive scheduler that exploits simultaneous processing among the devices can improve performance up to a factor of 8 × compared to the best alternative solutions that only use the CPU cores or the FPGA fabric. Moreover, our proposal achieves up to 15% and 37% of improvement compared to the best heterogeneous solutions found with a dynamic and static schedulers, respectively.
Keywords: pc2-harp-ressources

FPGA-Accelerated Optimistic Concurrency Control for Transactional Memory - Li, Zhaoshi; Liu, Leibo; Deng, Yangdong; Wang, Jiawei; Liu, Zhiwei; Yin, Shouyi; Wei, Shaojun (Proceedings of the 52nd Annual IEEE/ACM International Symposium on Microarchitecture)
Transactional Memory (TM) has been considered as a promising alternative to existing synchronization operations, which are often the largest stumbling block to unleashing parallelism of applications. Efficient implementations of TM, however, are challenging due to the tension between lowering performance overhead and avoiding unnecessary aborts. In this paper, we present Reachability-based Optimistic Concurrency Control for Transactional Memory (ROCoCoTM), a novel scheme which offloads concurrency control (CC) algorithms, the central building blocks of TM systems, to reconfigurable hardware. To reduce the abort rate, an innovative formalization of mainstream CC algorithms is developed to reveal a common restriction that leads to unnecessary aborts. This restriction is resolved by the ROCoCo algorithm with a centralized validation phase, which can be efficiently pipelined in hardware. Thanks to a high-performance offloading engine implemented in reconfigurable hardware, ROCoCo algorithm results in decreased abort rates and reduced performance overhead. The whole system is implemented on Intel's HARP2 platform and evaluated with the STAMP benchmark suite. Experiments show 1.55x and 8.05x geomean speedup over TinySTM and an HTM based on Intel TSX, respectively. Given the fast-growing deployment of commodity CPU-FPGA platforms, ROCoCoTM paves the way for software programmers to exploit heterogeneous computing resources with a high-level transactional abstraction to effectively extract the parallelism in modern applications.
Keywords: pc2-harp-ressources

A PCB Integrated Winding Using a Litz Structure for a Wireless Charging Coil - Rehlaender, Philipp; Grote, Tobias; Tikhonov, Sergey; Niejende, Hugues; Schafmeister, Frank; Bocker, Joachim; Thiemann, Peter (2019 21st European Conference on Power Electronics and Applications (EPE '19 ECCE Europe))

Analytical Topology Comparison for a Single Stage On-Board EV-Battery Converter - Rehlaender, Philipp; Schafmeister, Frank; Bocker, Joachim; Grote, Tobias (2019 IEEE 28th International Symposium on Industrial Electronics (ISIE))

Traffic Sign Detection Using R-CNN - Rehlaender, Philipp; Schroeer, Maik; Chadha, Gavneet; Schwung, Andreas (Proceedings of the International Neural Networks Society)

Continuous relaxations for the traveling salesman problem - Sahai, Tuhin; Ziessler, Adrian; Klus, Stefan; Dellnitz, Michael (Nonlinear Dynamics)

Investigation on Inductive Heating of Sheet Metal for an Industrial Hot Stamping Process - Pfeifer, Florian; Dietrich, André; Marten, Thorsten; Tröster, Thomas; Nacke, Bernard (Proceedings of 7th International Conference on Hot Sheet Metal Forming of High-Performance Steel)

Energieabsorptions- und Versagensverhalten eines automobilen Seitenschwellers mit lokaler Verstärkung aus kohlenstofffaserverstärktem Kunststoff nach Alterung - Striewe, Jan André; Thomas, Robert; Fischer, Fabian; Wiens, Timo; Tröster, Thomas

Performance Parameters and HIP Routes for additively manufactured titanium alloy Ti6Al4V - Ahlers, Dominik; Tröster, Thomas

A holistic approach to the lightweight design of tailored structural components using the example of a hybrid A-pillar - Camberg, Alan Adam; Hielscher, Christian (Aachen Body Engineering Days 2019)

Challenges in fracture modeling under non-isothermal forming conditions using the example of a new forming process for aluminum blanks - Camberg, Alan Adam; Tröster, Thomas (26. Sächsische Fachtagung Umformtechnik)

A micromechanical based finite element simulation of process induced residual stresses in metal-CFRP-hybrid structures - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas

CLEF ProtestNews Lab 2019: Contextualized Word Embeddings for Event Sentence Detection and Event Extraction - Skitalinskaya, Gabriella; Klaﬀ, Jonas; Spliethöver, Maximilian
In this work we describe our results achieved in the ProtestNews Lab at CLEF 2019. To tackle the problems of event sentence detection and event extraction we decided to use contextualized string embeddings. The models were trained on a data corpus collected from Indian news sources, but evaluated on data obtained from news sources from other countries as well, such as China. Our models have obtained competitive results and have scored 3rd in the event sentence detection task and 1st in the event extraction task based on average F1-scores for diﬀerent test datasets.

Jump Search: A Fast Technique for the Synthesis of Approximate Circuits - Witschen, Linus Matthias; Ghasemzadeh Mohammadi, Hassan; Artmann, Matthias; Platzner, Marco (Fourth Workshop on Approximate Computing (AxC 2019))
State-of-the-art frameworks for generating approximate circuits usually rely on information gained through circuit synthesis and/or verification to explore the search space and to find an optimal solution. Throughout the process, a large number of circuits may be subject to processing, leading to considerable runtimes. In this work, we propose a search which takes error bounds and pre-computed impact factors into account to reduce the number of invoked synthesis and verification processes. In our experimental results, we achieved speed-ups of up to 76x while area savings remain comparable to the reference search method, simulated annealing.
Keywords: Approximate computing; parameter selection; search space exploration; verification; circuit synthesis

New Dimensions of Service Offshoring in World Trade - Atkins, Marc; Gilroy, Bernard Michael; Seiler, Volker (Intereconomics)

The Impact of Monetary Policy on Investment Bank Profitability in Unequal Economies - Gilroy, Bernard Michael; Golderbein, Alexander; Peitz, Christian; Stöckmann, Nico (Operations Research Proceedings 2018)

Social-Trading und Copy-Trading - Krimphove, Dieter; Peitz, Christian (Fintechs: Rechtliche Grundlagen moderner Finanztechnologien)

Evaporation sampled by stationary molecular dynamics simulation - Heinen, Matthias; Vrabec, Jadran (The Journal of Chemical Physics)
Keywords: pc2-ressources

Thermodynamic factor of quaternary mixtures from Kirkwood–Buff integration - Fingerhut, Robin; Herres, Gerhard; Vrabec, Jadran (Molecular Physics)
Keywords: pc2-ressources

Controlling the Electronic Contact at the Terpyridine/Metal Interface - Mennicken, Max; Peter, Sophia Katharina; Kaulen, Corinna; Simon, Ulrich; Karthäuser, Silvia (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

Negotiating Images of (Un-)Belonging and (Divided) Communities: Ali Smith's Seasonal Quartet as a Counter-Narrative to Brexit - Tönnies, Merle; Henneböhl, Dennis (Journal for the Study of British Cultures)

QM/MM Benchmarking of Cyanobacteriochrome Slr1393g3 Absorption Spectra - Wiebeler, Christian; Schapiro, Igor (Molecules)
Cyanobacteriochromes are compact and spectrally diverse photoreceptor proteins that are promising candidates for biotechnological applications. Computational studies can contribute to an understanding at a molecular level of their wide spectral tuning and diversity. In this contribution, we benchmark methods to model a 110 nm shift in the UV/Vis absorption spectrum from a red- to a green-absorbing form of the cyanobacteriochrome Slr1393g3. Based on an assessment of semiempirical methods to describe the chromophore geometries of both forms in vacuo, we find that DFTB2+D leads to structures that are the closest to the reference method. The benchmark of the excited state calculations is based on snapshots from quantum mechanics/molecular mechanics molecular dynamics simulations. In our case, the methods RI-ADC(2) and sTD-DFT based on CAM-B3LYP ground state calculations perform the best, whereas no functional can be recommended to simulate the absorption spectra of both forms with time-dependent density functional theory. Furthermore, the difference in absorption for the lowest energy absorption maxima of both forms can already be modelled with optimized structures, but sampling is required to improve the shape of the absorption bands of both forms, in particular for the second band. This benchmark study can guide further computational studies, as it assesses essential components of a protocol to model the spectral tuning of both cyanobacteriochromes and the related phytochromes.
Keywords: pc2-ressources

Digitaler Wandel als strategischer Transformationsprozess – Zum allgemeinen und hochschulspezifischen Verständnis der Digitalisierung - Oevel, Gudrun; Graf-Schlattmann, Marcel; Meister, Dorothee M.; Wilde, Melanie

Quo vadis, Fachinformationsdienste? Ein Überblick über die Ergebnisse der Evaluierung des Förderprogramms »Fachinformationsdienste« für die Wissenschaft - Oevel, Gudrun; Barlösius, Eva (Zeitschrift für Bibliothekswesen und Bibliographie)

Jump Search: A Fast Technique for the Synthesis of Approximate Circuits - Witschen, Linus Matthias; Ghasemzadeh Mohammadi, Hassan; Artmann, Matthias; Platzner, Marco (Proceedings of the 2019 on Great Lakes Symposium on VLSI - GLSVLSI '19)
State-of-the-art frameworks for generating approximate circuits automatically explore the search space in an iterative process - often greedily. Synthesis and verification processes are invoked in each iteration to evaluate the found solutions and to guide the search algorithm. As a result, a large number of approximate circuits is subjected to analysis - leading to long runtimes - but only a few approximate circuits might form an acceptable solution. In this paper, we present our Jump Search (JS) method which seeks to reduce the runtime of an approximation process by reducing the number of expensive synthesis and verification steps. To reduce the runtime, JS computes impact factors for each approximation candidate in the circuit to create a selection of approximate circuits without invoking synthesis or verification processes. We denote the selection as path from which JS determines the final solution. In our experimental results, JS achieved speed-ups of up to 57x while area savings remain comparable to the reference search method, Simulated Annealing.
Keywords: Approximate computing; design automation; parameter selection; circuit synthesis

Choice Functions Generated by Mallows and Plackett–Luce Relations - Tagne, V. K.; Fotso, S.; Fono, L. A.; Hüllermeier, Eyke (New Mathematics and Natural Computation)

On the Complexity of Local Graph Transformations - Scheideler, Christian; Setzer, Alexander (Proceedings of the 46th International Colloquium on Automata, Languages, and Programming)
We consider the problem of transforming a given graph G_s into a desired graph G_t by applying a minimum number of primitives from a particular set of local graph transformation primitives. These primitives are local in the sense that each node can apply them based on local knowledge and by affecting only its 1-neighborhood. Although the specific set of primitives we consider makes it possible to transform any (weakly) connected graph into any other (weakly) connected graph consisting of the same nodes, they cannot disconnect the graph or introduce new nodes into the graph, making them ideal in the context of supervised overlay network transformations. We prove that computing a minimum sequence of primitive applications (even centralized) for arbitrary G_s and G_t is NP-hard, which we conjecture to hold for any set of local graph transformation primitives satisfying the aforementioned properties. On the other hand, we show that this problem admits a polynomial time algorithm with a constant approximation ratio.
Keywords: Graphs transformations; NP-hardness; approximation algorithms

Koopman operator-based model reduction for switched-system control of PDEs - Peitz, Sebastian; Klus, Stefan (Automatica)
We present a new framework for optimal and feedback control of PDEs using Koopman operator-based reduced order models (K-ROMs). The Koopman operator is a linear but infinite-dimensional operator which describes the dynamics of observables. A numerical approximation of the Koopman operator therefore yields a linear system for the observation of an autonomous dynamical system. In our approach, by introducing a finite number of constant controls, the dynamic control system is transformed into a set of autonomous systems and the corresponding optimal control problem into a switching time optimization problem. This allows us to replace each of these systems by a K-ROM which can be solved orders of magnitude faster. By this approach, a nonlinear infinite-dimensional control problem is transformed into a low-dimensional linear problem. Using a recent convergence result for the numerical approximation via Extended Dynamic Mode Decomposition (EDMD), we show that the value of the K-ROM based objective function converges in measure to the value of the full objective function. To illustrate the results, we consider the 1D Burgers equation and the 2D Navier–Stokes equations. The numerical experiments show remarkable performance concerning both solution times and accuracy.

On the hierarchical structure of Pareto critical sets - Gebken, Bennet; Peitz, Sebastian; Dellnitz, Michael (Journal of Global Optimization)
In this article we show that the boundary of the Pareto critical set of an unconstrained multiobjective optimization problem (MOP) consists of Pareto critical points of subproblems where only a subset of the set of objective functions is taken into account. If the Pareto critical set is completely described by its boundary (e.g., if we have more objective functions than dimensions in decision space), then this can be used to efficiently solve the MOP by solving a number of MOPs with fewer objective functions. If this is not the case, the results can still give insight into the structure of the Pareto critical set.

Finite-Control-Set Model Predictive Control for a Permanent Magnet Synchronous Motor Application with Online Least Squares System Identification - Hanke, Soren; Peitz, Sebastian; Wallscheid, Oliver; Böcker, Joachim; Dellnitz, Michael (2019 IEEE International Symposium on Predictive Control of Electrical Drives and Power Electronics (PRECEDE))
In comparison to classical control approaches in the field of electrical drives like the field-oriented control (FOC), model predictive control (MPC) approaches are able to provide a higher control performance. This refers to shorter settling times, lower overshoots, and a better decoupling of control variables in case of multi-variable controls. However, this can only be achieved if the used prediction model covers the actual behavior of the plant sufficiently well. In case of model deviations, the performance utilizing MPC remains below its potential. This results in effects like increased current ripple or steady state setpoint deviations. In order to achieve a high control performance, it is therefore necessary to adapt the model to the real plant behavior. When using an online system identification, a less accurate model is sufficient for commissioning of the drive system. In this paper, the combination of a finite-control-set MPC (FCS-MPC) with a system identification is proposed. The method does not require high-frequency signal injection, but uses the measured values already required for the FCS-MPC. An evaluation of the least squares-based identification on a laboratory test bench showed that the model accuracy and thus the control performance could be improved by an online update of the prediction models.

Assessing the long-term fragmentation of information systems research with a longitudinal multi-network analysis - Khan, Gohar Feroz; Trier, Matthias (European Journal of Information Systems)

Argument Search: Assessing Argument Relevance - Potthast, Martin; Gienapp, Lukas; Euchner, Florian; Heilenkötter, Nick; Weidmann, Nico; Wachsmuth, Henning; Stein, Benno; Hagen, Matthias (42nd International ACM Conference on Research and Development in Information Retrieval (SIGIR 2019))

Book Review: Argumentation Mining - Wachsmuth, Henning (Computational Linguistics)

Data Acquisition for Argument Search: The args.me Corpus - Ajjour, Yamen; Wachsmuth, Henning; Kiesel, Johannes; Potthast, Martin; Hagen, Matthias; Stein, Benno (Proceedings of the 42nd Edition of the German Conference on Artificial Intelligence)

Zynq-based acceleration of robust high density myoelectric signal processing - Boschmann, Alexander; Agne, Andreas; Thombansen, Georg; Witschen, Linus Matthias; Kraus, Florian; Platzner, Marco (Journal of Parallel and Distributed Computing)
Advances in electromyographic (EMG) sensor technology and machine learning algorithms have led to an increased research effort into high density EMG-based pattern recognition methods for prosthesis control. With the goal set on an autonomous multi-movement prosthesis capable of performing training and classification of an amputee’s EMG signals, the focus of this paper lies in the acceleration of the embedded signal processing chain. We present two Xilinx Zynq-based architectures for accelerating two inherently different high density EMG-based control algorithms. The first hardware accelerated design achieves speed-ups of up to 4.8 over the software-only solution, allowing for a processing delay lower than the sample period of 1 ms. The second system achieved a speed-up of 5.5 over the software-only version and operates at a still satisfactory low processing delay of up to 15 ms while providing a higher reliability and robustness against electrode shift and noisy channels.
Keywords: High density electromyography; FPGA acceleration; Medical signal processing; Pattern recognition; Prosthetics

A Value-Centered Approach for Unique and Novel Software Applications - Senft, Björn; Rittmeier, Florian; Fischer, Holger Gerhard; Oberthür, Simon (Design, User Experience, and Usability. Practice and Case Studies)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Reconfigurable metasurface hologram by utilizing addressable dynamic pixels - Li, Tianyou; Wei, Qunshuo; Reineke, Bernhard; Walter, Felicitas; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Optics Express)

Unsupervised training of neural mask-based beamforming - Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold (INTERSPEECH 2019, Graz, Austria)
We present an unsupervised training approach for a neural network-based mask estimator in an acoustic beamforming application. The network is trained to maximize a likelihood criterion derived from a spatial mixture model of the observations. It is trained from scratch without requiring any parallel data consisting of degraded input and clean training targets. Thus, training can be carried out on real recordings of noisy speech rather than simulated ones. In contrast to previous work on unsupervised training of neural mask estimators, our approach avoids the need for a possibly pre-trained teacher model entirely. We demonstrate the effectiveness of our approach by speech recognition experiments on two different datasets: one mainly deteriorated by noise (CHiME 4) and one by reverberation (REVERB). The results show that the performance of the proposed system is on par with a supervised system using oracle target masks for training and with a system trained using a model-based teacher.

Efficient Multi-Channel Simulation of Wireless Communications - Bronner, Fabian; Sommer, Christoph (2018 IEEE Vehicular Networking Conference (VNC))

Verkehrssimulation im Hardware-in-the-Loop-Steuergerätetest - Reinold, Peter; Meyer, Norbert; Buse, Dominik; Klingler, Florian; Sommer, Christoph; Dressler, Falko; Eisenbarth, Markus; Andert, Jakob (Proceedings)

Veins: The Open Source Vehicular Network Simulation Framework - Sommer, Christoph; Eckhoff, David; Brummer, Alexander; Buse, Dominik S.; Hagenauer, Florian; Joerer, Stefan; Segata, Michele (Recent Advances in Network Simulation)

A Context-aware Virtual Reality First Aid Training Application - Yigitbas, Enes; Heindörfer, Joshua; Engels, Gregor (Proceedings of the Mensch und Computer 2019 (MuC ’19))

Steuerkomplexität im Vergleich zwischen Deutschland und Österreich – Eine Analyse des Status quo - Hoppe, Thomas; Rechbauer, Martina; Sturm, Susann
Die Komplexität von Steuersystemen gewinnt in der Debatte um den internationalen Steuerwettbewerb zunehmend an Bedeutung. Im vorliegenden Beitrag erfolgt, basierend auf den Daten, die dem Tax Complexity Index (www.taxcomplexity.org) zugrunde liegen, eine umfassende Gegenüberstellung der Komplexität der Steuersysteme von Deutschland und Öster-reich unter Berücksichtigung der Mittelwerte aller Länder. Die Steuergesetze weisen sowohl in Deutschland als auch in Österreich einen verhältnismäßig hohen Grad an Komplexität auf. Bei den steuerlichen Rahmenbedingungen fällt der Grad an Komplexität in beiden Ländern dagegen niedrig aus, wobei Österreich im Durchschnitt weniger komplex ist als Deutschland.

Managing Multiple Mobile Resources - Feldkord, Björn; Knollmann, Till; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 17th Workshop on Approximation and Online Algorithms (WAOA))

Unsupervised Training of a Deep Clustering Model for Multichannel Blind Source Separation - Drude, Lukas; Hasenklever, Daniel; Haeb-Umbach, Reinhold (ICASSP 2019, Brighton, UK)
We propose a training scheme to train neural network-based source separation algorithms from scratch when parallel clean data is unavailable. In particular, we demonstrate that an unsupervised spatial clustering algorithm is sufficient to guide the training of a deep clustering system. We argue that previous work on deep clustering requires strong supervision and elaborate on why this is a limitation. We demonstrate that (a) the single-channel deep clustering system trained according to the proposed scheme alone is able to achieve a similar performance as the multi-channel teacher in terms of word error rates and (b) initializing the spatial clustering approach with the deep clustering result yields a relative word error rate reduction of 26% over the unsupervised teacher.

Joint Optimization of Neural Network-based WPE Dereverberation and Acoustic Model for Robust Online ASR - Heymann, Jahn; Drude, Lukas; Haeb-Umbach, Reinhold; Kinoshita, Keisuke; Nakatani, Tomohiro (ICASSP 2019, Brighton, UK)
Signal dereverberation using the Weighted Prediction Error (WPE) method has been proven to be an effective means to raise the accuracy of far-field speech recognition. First proposed as an iterative algorithm, follow-up works have reformulated it as a recursive least squares algorithm and therefore enabled its use in online applications. For this algorithm, the estimation of the power spectral density (PSD) of the anechoic signal plays an important role and strongly influences its performance. Recently, we showed that using a neural network PSD estimator leads to improved performance for online automatic speech recognition. This, however, comes at a price. To train the network, we require parallel data, i.e., utterances simultaneously available in clean and reverberated form. Here we propose to overcome this limitation by training the network jointly with the acoustic model of the speech recognizer. To be specific, the gradients computed from the cross-entropy loss between the target senone sequence and the acoustic model network output is backpropagated through the complex-valued dereverberation filter estimation to the neural network for PSD estimation. Evaluation on two databases demonstrates improved performance for on-line processing scenarios while imposing fewer requirements on the available training data and thus widening the range of applications.

Directional Statistics and Filtering Using libDirectional - Kurz, Gerhard; Gilitschenski, Igor; Pfaff, Florian; Drude, Lukas; Hanebeck, Uwe D.; Haeb-Umbach, Reinhold; Siegwart, Roland Y. (Journal of Statistical Software 89(4))
In this paper, we present libDirectional, a MATLAB library for directional statistics and directional estimation. It supports a variety of commonly used distributions on the unit circle, such as the von Mises, wrapped normal, and wrapped Cauchy distributions. Furthermore, various distributions on higher-dimensional manifolds such as the unit hypersphere and the hypertorus are available. Based on these distributions, several recursive filtering algorithms in libDirectional allow estimation on these manifolds. The functionality is implemented in a clear, well-documented, and object-oriented structure that is both easy to use and easy to extend.

Sparse Adaptation of Distributed Blind Source Separation in Acoustic Sensor Networks - Guenther, Michael; Afifi, Haitham; Brendel, Andreas; Karl, Holger; Kellermann, Walter (2019 IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (WASPAA) (WASPAA 2019))
By distributing the computational load over the nodes of a Wireless Acoustic Sensor Network (WASN), the real-time capability of the TRINICON (TRIple-N-Independent component analysis for CONvolutive mixtures) framework for Blind Source Separation (BSS) can be ensured, even if the individual network nodes are not powerful enough to run TRINICON in real-time by themselves. To optimally utilize the limited computing power and data rate in WASNs, the MARVELO (Multicast-Aware Routing for Virtual network Embedding with Loops in Overlays) framework is expanded for use with TRINICON, while a feature-based selection scheme is proposed to exploit the most beneficial parts of the input signal for adapting the demixing system. The simulation results of realistic scenarios show only a minor degradation of the separation performance even in heavily resource-limited situations.

An Approximate Power Control Algorithm for a Multi-Cast Wireless Virtual Network Embedding - Afifi, Haitham; Karl, Holger (2019 12th IFIP Wireless and Mobile Networking Conference (WMNC) (WMNC'19))
Internet of Things (IoT) applications witness an exceptional evolution of traffic demands, while existing protocols, as seen in wireless sensor networks (WSNs), struggle to cope with these demands. Traditional protocols rely on finding a routing path between sensors generating data and sinks acting as gateway or databases. Meanwhile, the network will suffer from high collisions in case of high data rates. In this context, in-network processing solutions are used to leverage the wireless nodes' computations, by distributing processing tasks on the nodes along the routing path. Although in-network processing solutions are very popular in wired networks (e.g., data centers and wide area networks), there are many challenges to adopt these solutions in wireless networks, due to the interference problem. In this paper, we solve the problem of routing and task distribution jointly using a greedy Virtual Network Embedding (VNE) algorithm, and consider power control as well. Through simulations, we compare the proposed algorithm to optimal solutions and show that it achieves good results in terms of delay. Moreover, we discuss its sub-optimality by driving tight lower bounds and loose upper bounds. We also compare our solution with another wireless VNE solution to show the trade-off between delay and symbol error rate.

A Rapid Prototyping for Wireless Virtual Network Embedding using MARVELO - Afifi, Haitham; Karl, Holger; Eikenberg, Sebastian; Mueller, Arnold; Gansel, Lars; Makejkin, Alexander; Hannemann, Kai; Schellenberg, Rafael (2019 IEEE Wireless Communications and Networking Conference (WCNC) (IEEE WCNC 2019) (Demo))
One of the major challenges in implementing wireless virtualization is the resource discovery. This is particularly important for the embedding-algorithms that are used to distribute the tasks to nodes. MARVELO is a prototype framework for executing different distributed algorithms on the top of a wireless (802.11) ad-hoc network. The aim of MARVELO is to select the nodes for running the algorithms and to define the routing between the nodes. Hence, it also supports monitoring functionalities to collect information about the available resources and to assist in profiling the algorithms. The objective of this demo is to show how MAVRLEO distributes tasks in an ad-hoc network, based on a feedback from our monitoring tool. Additionally, we explain the work-flow, composition and execution of the framework.
Keywords: WSN; virtualization; VNE

Analyzing Data Usage in Array Programs - Haltermann, Jan Frederik